2011
DOI: 10.3109/17435390.2011.572301
|View full text |Cite
|
Sign up to set email alerts
|

Development of a PIXE analysis method for the determination of the biopersistence of SiC and TiC nanoparticles in rat lungs

Abstract: With the advent of nanoparticles produced in high quantities and employed in products or processes, the need to evaluate their potential toxicological effects is necessary. For this purpose, biopersistence studies are needed to assess the possible effects of nanoparticles in parallel with a proper characterization. The insoluble character of many nanomaterials makes traditional chemical analytical methods unapplicable for the ex-vivo measurements of their concentration in organs. Ion beam-based techniques such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…The discrepancy between the average diameter of PEI-SPIONs as determined by TEM and ZetaPALS can be explained by the agglomeration of charged PEI-SPIONs in the preparation of sample solution for ZetaPALS analysis. [31][32][33] These results demonstrated that PEI-SPIONs/PST complex is still positively charged and suitable for cellular internalization.…”
mentioning
confidence: 69%
“…The discrepancy between the average diameter of PEI-SPIONs as determined by TEM and ZetaPALS can be explained by the agglomeration of charged PEI-SPIONs in the preparation of sample solution for ZetaPALS analysis. [31][32][33] These results demonstrated that PEI-SPIONs/PST complex is still positively charged and suitable for cellular internalization.…”
mentioning
confidence: 69%
“…The fetus is known to be susceptible to various toxic substances [1, 15, 39]. Therefore, there is high concern regarding exposure to exogenous substances, including nanosized materials, for pregnant women [12, 32, 39]. …”
mentioning
confidence: 99%
“…This difference is due to the higher level of noise present at low energies, including the energy range of the Si peak, due to the bremsstrahlung effect. The methodology and setup for PIXE measurements of NPs in solid matrices has been reported recently by Lozano et al [12], positioning then PIXE as a powerful tool to measure NPs without altering their original matrices/media. Currently, we are actively looking for better approaches to the measurements in order to reduce the LODs to measurable levels of at least microgram per millilitre, a concentration range covering most of the in vitro toxicological assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Data was processed with the software GUPIXWIN v2.2.3 [14], which takes into account the absorption of Xrays due to matrix effects. An explanation of the physical principles of PIXE can be found elsewhere [12,15], but briefly: when a sample is irradiated with an ion beam (i.e. protons), it emits X-rays for each present element.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation